Potential antimicrobial activities of belimbing buluh (averrhoa bilimbi) leaves extracts against common human pathogens / Ainun Jariah Manaf, Neni Kartini Che Mohd Ramli and Nur Izzati Hairuddin - Manaf, Ainun Jariah; Che Mohd Ramli, Neni Kartini; Hairuddin, Nur Izzati (2015)
From ancient times plants have provided a source of inspiration for novel drug compounds, as plant-derived medicines have made large contributions to human health. Traditional medicines by using herbs have been practiced by Malay communities from the past until now. The knowledge on the benefits of certain herbs has been passed from generation to generation. The primary health care of 80% of the world's population is based on the use of medicinal plants derived from traditional system of medicine and local health practices. Averrhoa bilimbi is a member of the family Oxalidaceae known as "bilimbi" and native in Malaysia and Indonesian Moluccas. The plant has an enormous fiscal value since most of the plant parts such as leaves, bark, flowers, fruits, seeds and roots which are used as an alternative medicine to treat a variety of diseases. Thus, this study was conducted to investigate the potential antibacterial and antifungal activities of Averrhoa bilimbi leaves extracts against selected human pathogens. A. bilimbi leaves were extracted by using two polar solvents i.e. water and methanol. Two strains of bacteria, Staphylococcus aureus and Bacillus subtilis and two species of human pathogenic fungi, Candida albicans and Aspergillus niger were used to screen the antimicrobial activity and antifungal activity of A. bilimbi by well diffusion method. The minimal inhibitory concentration were determined by using different concentrations of leaves extracts (50, 100, 200, 400, 600, 800 µg/ml) using the same method. The phytochemical analyses of the leaves extracts were also conducted to determine the secondary metabolites presented in the A. bilimbi leaves extracts. Ampicilin and Ketonozole were used for positive control of antifungal and antibacterial activities respectively. Findings showed that methanol leaves extract gave larger zone of inhibition compared to water leaves extracts against 50 aureus and E. coli with 6.0 mm and 7.0 mm respectively compared to 1.4 mm and 1.6 mm zone of inhibitions respectively at the same concentration (600 ug/uL). Meanwhile, for antifungal activities, methanol leaves extract showed higher zone of inhibition against C. albican compared to water leaves extract with 1.9mm and 1.2mm zone of inhibition respectively at the same concentration (200 ug/uL). However, there was no inhibition showed by A. niger for both of the leaves extracts. The Minimal Inhibitory Concentration (MIC) of methanol leaves extracts for antibacterial activity against S. aureus was at 600 ug/uL (6.0 mm) and E. coli was at 800 ug/uL (9.2 mm) and for antifungal activity against C. albican was at 200 ug/uL (1.9 mm). Meanwhile the MIC for water leaves extract for antibacterial activity was at 800 ug/uL (S. aureus) and 200 ug/uL (E. coli) and for antifungal activity against C. albican was at 800 ug/uL. The phytochemical analysis found that the A. bilimbi leaves extracts to contain Alkaloid, Glycoside, Flavonoid, Saponin, Tannin, Triterpene and Phenol. The antimicrobial and antifungal activities of the A. bilimbi were due to the presence of various secondary metabolites. Therefore, these plants can be used to develop new pharmaceuticals products and other research activities.